Pup Directed Vocalizations of Adult Females and Males in a Vocal Learning Bat - Fernandez, Ahana Aurora; Knörnschild, Mirjam (Frontiers in Ecology and Evolution, 2020)
Social feedback plays an important role in human language development and in the vocal ontogeny of non-human animals. A special form of vocal feedback in humans, infant-directed speech – or motherese –facilitates language learning and is socially beneficial by increasing attention and arousal in the child. It is characterized by high pitch, expanded intonation contours and slower speech tempo. Furthermore, the vocal timbre (i.e. ’color’ of voice) of motherese differs from the timbre of adult-directed speech. In animals, pup-directed vocalizations are very common, especially in females. But so far there is hardly any research on whether there is a similar phenomenon as motherese in animal vocalizations. The greater sac-winged bat, Saccopteryx bilineata, is a vocal production learner with a large vocal repertoire that is acquired during ontogeny. We compared acoustic features between female pup-directed and adult-directed vocalizations and demonstrated that they differed in timbre and peak frequency. Furthermore, we described pup-directed vocalizations of adult males. During the ontogenetic period when pups’ isolation calls (used to solicit maternal care) are converging towards each other to form a group signature, adult males also produce isolation calls. Pups’ isolation calls are acoustically more similar to those of males from the same social group than to other males. In conclusion, our novel findings indicate that parent-offspring communication in bats is more complex and multifaceted than previously thought, with female pup-directed vocalizations reminiscent of human motherese and male pup-directed vocalizations that may facilitate the transmission of a vocal signature across generations.